Expansion of Circulating T Follicular Helper Cells in Children with Acute Henoch-Schönlein Purpura - Jue Xie; Yan Liu; Lei Wang; Guoxiang Ruan; Huiming Yuan; Hong Fang; Jianyong Wu; Dawei Cui (Journal of Immunology Research)
Henoch-Schönlein purpura (HSP) is a common systemic small vessel vasculitis in children with disorder autoimmune responses. T follicular helper (TFH) cells play crucial roles in regulating immune responses. The aim of our study was to investigate the probable role of TFH cells in the pathogenesis of children with HSP. In this study, the frequency of circulating CXCR5+CD4+TFH cells with inducible costimulator (ICOS) expression in the children with acute HSP was significantly higher than that in healthy controls (HCs) but not CXCR5+CD4+TFH cells with programmed death-1 (PD-1) expression. Moreover, serum levels of IL-21 and IL-6 cytokines, IgA, and C3 in HSP children were also significantly higher than those in HCs. A positive correlation was observed between the frequencies of circulating ICOS+CXCR5+CD4+TFH cells and the serum IL-21 or IgA levels of acute HSP children, respectively. Additionally, the mRNA expression levels of interleukin- (IL-) 21, IL-6, and transcriptional factors (B-cell lymphoma-6, Bcl-6) were also significantly increased in peripheral blood from acute HSP children compared to HCs. Taken together, these findings suggest that TFH cells and associated molecules might play critical roles in the pathogenesis of HSP, which are possible therapeutic targets in HSP children.